Cytokine-like activity of European sea bass ISG15 protein on RGNNV-infected E−11 cells - Moreno-García, Patricia; Leiva-Rebollo, Rocío; García-Rosado, Esther; Béjar-Alvarado, Julia; Alonso-Sánchez, María del Carmen (Elsevier, 2022)
IFN-I generates an antiviral state by inducing the expression of numerous genes, called IFN-stimulated genes, ISGs, including ISG15, which is the only ISG with cytokine-like activity. In a previous study, we developed the Dl_ISG15_E11 cell line, which consisted of E11 cells able to express and secrete sea bass ISG15. The current study is a step forward, analysing the effect of secreted sea bass ISG15 on RGNNV replication in E11 cells, and looking into its immunomodulatory activity in order to corroborate its cytokine-like activity. The medium from ISG15- produccing cells compromised RGNNV replication, as it has been demonstrated both, by reduction in the viral genome synthesis and, specially, in the yield of infective viral particles. The implication of sea bass ISG15 in this protection has been demonstrated by ISG15 removal, which decreased the percentage of surviving cells upon viral infection, and by incubation of RGNNV-infected cells with a recombinant sea bass ISG15 protein, which resulted in almost full protection. Furthermore, the immunomodulatory activity of extracellular sea bass ISG15 has been demonstrated, which reaffirms a cytokine-like role for this protein
Keywords: Lubinas; ISG15; European sea bass; Dicentrarchus labrax E; E−11 cells; Antiviral immune system; RGNNV; IFN-I system